2020
DOI: 10.3390/toxins12070430
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activity of Bacillus thuringiensis Proteins against Coleopteran Pests

Abstract: Bacillus thuringiensis is the most successful microbial insecticide agent and its proteins have been studied for many years due to its toxicity against insects mainly belonging to the orders Lepidoptera, Diptera and Coleoptera, which are pests of agro-forestry and medical-veterinary interest. However, studies on the interactions between this bacterium and the insect species classified in the order Coleoptera are more limited when compared to other insect orders. To date, 45 Cry proteins, 2 Cyt proteins, 11 Vip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 187 publications
(213 reference statements)
0
46
1
1
Order By: Relevance
“…Mortality caused by Cry34/35Ab1 is more likely chronic in nature and relies on a myriad of secondary factors (disease, predation, abiotic stress) 36 . These differences seen in larval susceptibility and the development of resistance to Cry34/35Ab1 could be due to the differences in structure of the binary Cry34/35Ab1 δ‐endotoxin 62 compared to the ternary structure of Cry3Bb1, eCry3.1Ab and mCry3A δ‐endotoxins 63 . The latter three proteins have distinct binding sites, 64–67 and previous studies have shown a lack of cross resistance between Cry34/35Ab1 and other proteins 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Mortality caused by Cry34/35Ab1 is more likely chronic in nature and relies on a myriad of secondary factors (disease, predation, abiotic stress) 36 . These differences seen in larval susceptibility and the development of resistance to Cry34/35Ab1 could be due to the differences in structure of the binary Cry34/35Ab1 δ‐endotoxin 62 compared to the ternary structure of Cry3Bb1, eCry3.1Ab and mCry3A δ‐endotoxins 63 . The latter three proteins have distinct binding sites, 64–67 and previous studies have shown a lack of cross resistance between Cry34/35Ab1 and other proteins 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Although Coleopteran pests are numerous in forest ecosystems, relatively few have been tested for their susceptibility to Bt toxins. Moreover, among studies examining Bt effectiveness against Coleopteran insects, beetles in the family Chrysomelidae are overrepresented while Curculionidae (weevil) species have been less examined 15,16 . A moderate proportion of those Curculionidae species investigated have shown susceptibility to Bt , but few toxins have been tested 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, among studies examining Bt effectiveness against Coleopteran insects, beetles in the family Chrysomelidae are overrepresented while Curculionidae (weevil) species have been less examined. 15,16 A moderate proportion of those Curculionidae species investigated have shown susceptibility to Bt, but few toxins have been tested. 15,16 The most commonly tested Cry proteins include Cry3Aa (Bt ssp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current knowledge about Vip proteins has also been reviewed [ 2 ], as has the contribution that the use of toxin mutants has made to the knowledge of the mode of action of the three-domain Cry proteins [ 3 ]. On the other hand, two more review papers recapitulate the information on the cytocidal activity of Bt proteins [ 4 ] or the insecticidal activity of Bt proteins against coleopteran pests [ 5 ]. All these review papers are of high value, allowing readers to stay updated on the different aspects of the Bt field described here.…”
mentioning
confidence: 99%